Mengoptimalkan Motivasi Belajar: Pengaruh Signifikan Kualitas Pendidikan dan Kepuasan Mahasiswa - Bakti, Ferry; Dendi, Agus; Amir, Ari; Isnanto, Burham (Nomico, 2024)
The quality of education is a major concern in academia and is often associated with student satisfaction and learning motivation. This study aims to analyze the effect of teaching quality, educational facilities, and administrative services on student satisfaction, as well as the impact on learning motivation in the context of higher education in Indonesia. Using the survey method, data was collected from 160 students at the ISB Atmaluhur Pangkalpinang campus. Data analysis was performed using structural equation modeling (SEM) and SPSS to test the research hypothesis. The results showed that the quality of teaching, educational facilities, and administrative services had a positive and significant effect on student satisfaction, both partially and simultaneously. In addition, student satisfaction also has a positive and significant effect on learning motivation. These findings broaden understanding of the factors that influence student satisfaction and learning motivation, and emphasize the importance of a holistic approach in improving the quality of higher education. The practical implications of this research include the need for higher education institutions to focus on improving the quality of teaching, providing adequate educational facilities, and improving the quality of administrative services to achieve optimal student satisfaction and encourage higher learning motivation.